2020
DOI: 10.1037/pro0000308
|View full text |Cite
|
Sign up to set email alerts
|

Therapist factors related to the treatment of adolescent eating disorders.

Abstract: Eating disorders (EDs) are historically complex to treat, and evidence-based recommendations for treating adolescents with EDs need to be improved. The present study is unique and distinctive as it is the first to assess therapists' report of their technique, working alliance, and countertransference with ED adolescents in relation to patient factors of childhood traumatic experiences as well as ED symptomatology. One hundred and four experienced (M ϭ 16.28 years as clinician) therapists from a variety of diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Additionally, our study’s finding that therapists rated early session alliance higher with patients reporting anxiety, specifically trauma-related stress, is also consistent with extant literature on working with patients with a trauma history. For example, in a study by Groth et al (2020) therapists reported experiencing more special and involved personal feelings with patients of greater trauma severity. In work by Reynolds et al (2017), researchers found that in a chronic, complex trauma sample, patients’ adaptive coping strategies were significant predictors of positive therapist ratings of alliance.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, our study’s finding that therapists rated early session alliance higher with patients reporting anxiety, specifically trauma-related stress, is also consistent with extant literature on working with patients with a trauma history. For example, in a study by Groth et al (2020) therapists reported experiencing more special and involved personal feelings with patients of greater trauma severity. In work by Reynolds et al (2017), researchers found that in a chronic, complex trauma sample, patients’ adaptive coping strategies were significant predictors of positive therapist ratings of alliance.…”
Section: Discussionmentioning
confidence: 99%
“…Substantial evidence highlights the alliance–outcome association (Graves et al, 2017; Zaitsoff et al, 2015), but far less is known about factors contributing to (or hindering) the development of a strong alliance among patients with EDs (Constantino et al, 2005; Groth et al, 2020; Katznelson et al, 2020; Waller et al, 2012; Zaitsoff et al, 2008). By identifying such factors, therapists can better predict potential relationship ruptures and tailor their interventions to prevent them (Safran et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…With respect to the latter point, future studies should evaluate more comprehensive and reliable outcome indices. Such investigations might explore changes in personality functioning, as well as the potential indirect effects of the therapeutic alliance or therapist effects on ED treatment outcome (e.g., Colli et al, 2016;Lingiardi et al, 2018;Tanzilli et al, 2018;Groth et al, 2020). Lastly, some authors (e.g., Lilenfeld et al, 2006) have noted that it is difficult to differentiate the pathoplasty model from the so-called predispositional model.…”
Section: Discussionmentioning
confidence: 99%